Pajak Aceh - Mahdi Syahbandir (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: Aceh Taxation is one of the regional revenues in terms of financing Aceh’s Autonomy. A way that can be achieved in increasing the revenue is by intensifying object and subject of regional taxes. Theoretically and based on the experience in collecting it, the imposition of higher tax, is not always resulting in maximal revenue. It is better by the model of Leviathan that becomes a consideration of Aceh Governance in collecting it. The model tells that the improvement of the tax should not be obtained by burdening higher tax but by the lower one and it is combined with the intensification of subject and object of the tax in order to get maxmimal revenue. The tax is based on Qanun (Aceh’s Local Law) Number 2, 2012 that has imposed progressive rate, especially for vehicles. Meanwhile, other taxes apply proportional rate. The number of rate applied is lower that the highest rate allowed by the Act Number 28, 2009. However, it is timed by the basis of tax imposition; the number of unpayable tax is still high. The Aceh Tax